Effect of Floor Cooling on Behavior and Heart Rate of Late Lactation Sows Under Acute Heat Stress - Parois, Severine P.; Cabezón, Francisco A.; Schinckel, Allan P.; Johnson, Jay S.; Stwalley, Robert M.; Marchant-Forde, Jeremy N. (Frontiers in Veterinary Science, 2018)
Much U.S. swine production is in Köppen climate types classified as ‘hot-summer humid continental’ and ‘humid subtropical’. As a result, farrowing sows are often exposed to temperatures above their upper critical temperature. This heat stress (HS) can affect sow welfare and productivity and have a negative economic impact. The study objective was to evaluate the impact of a cooling pad on sows’ behavioral and heart rate responses to acute HS. Treatments were randomly allotted to 10 multiparous sows to receive a constant cool water flow of 0.00 (CONTROL, n=4), 0.25 (LOW, n=2), 0.55 (MEDIUM, n=2) or 0.85 (HIGH, n=2) L/min for 100 min and replicated eight times, switching treatments so that each sow was exposed to each treatment. The cooling was initiated 1 hour after the room reached 35°C for 100 min. Eating, drinking and nursing behaviors, postures and heart rate were recorded before heating (Period 1), prior to cooling (Period 2), and during cooling (Period 3). There were no differences between LOW, MEDIUM and HIGH flow rates for any periods on all behavioral and heart rate traits, so data were pooled (COOLED). There were no differences in any of the measures during Periods 1 and 2, except for the ratio of short term to long term heart rate variability (SD1:SD2) with higher values for CONTROL than COOLED sows in Period 2. During Period 3, CONTROL sows changed postures more frequently (11.5±1.6 vs 5.1±1.6 changes per hour), spent more time drinker-pressing/drinking (4.4±0.5 vs 1.4±0.4% of time), standing (6.6±1.7 vs 3.8±1.6% of time), sitting (10.0±1.2 vs 4.0±1.1), less time lying (83.0±1.8 vs 92.0±1.7% of time), especially lying laterally (62.0±5.6 vs 75.0±5.3% of time), than sows in all three cooling treatments (all P < 0.001). Heart rate during Period 3 was lower for COOLED sows compared to the CONTROL sows (100.2±3.4 vs 119.0±4.0 beat per min, P<0.001). Sows response to increased thermal load can be effectively reduced using water-cooled cooling pads, thereby improving sow comfort and welfare. The beneficial effects on behavior are noticeable from the lowest flow rate.